Impact of Discontinuation of Antiplatelet Therapy Prior to Isolated Valve and Combined Coronary Artery Bypass Graft and Valve Procedures on Short and Intermediate Term Outcomes - Meneguzzi, J.; Kilpin, M.; Zhu, Y.; Doi, A.; Reid, Christopher; Tran, L.; Hayward, P.; Smith, J. (Elsevier, 2017)
© 2017. Background: A change in cardiac surgery practice over the past decade has seen an increase in urgent or inpatient referrals for surgery, with antiplatelet therapy often continued up until surgery. This study aims to identify the optimal timing for administration of aspirin to minimise risk of perioperative morbidity and mortality. Methods: From a prospectively compiled database collected by the Australian and New Zealand Society of Cardiac and Thoracic Surgeons, we identified 8,294 patients undertaking combined CABG and valve or isolated valve procedures while discontinuing aspirin. Time points for cessation of antiplatelet therapy were categorised as follows: < 2 days, 3-7 days or > 7 days preoperatively. We evaluated the association of adverse in-hospital events and intermediate term survival in each time category. Results: Discontinuing aspirin three to seven days from surgery decreased rates of perioperative MI (HR = 0.300, p = 0.027), return to theatre (HR = 0.560, p = 0.002) reduced drain output (HR = 0.757, p = 0.000) and red blood cell and platelet transfusions (HR = 0.719, p = 0.000 and HR = 0.604, p = 0.000 respectively) compared to patients continuing aspirin until < 2 days from the procedure.Stopping aspirin < 2 days from the date of surgery increased risk of perioperative MI (HR = 5.919, p = 0.000), reoperation for bleeding (HR = 2.076, p = 0.001), returning to theatre (HR = 1.781, p = 0.000), ICC drain losses (HR = 1.337, p = 0.000) and transfusion demands for red blood cells (HR = 1.381, p = 0.000) and platelets (HR = 1.450, p = 0.000) when compared to those discontinuing aspirin > 7 days from surgery. Conclusion: Late discontinuation of aspirin before combined coronary artery bypass graft and valve procedures results in greater rates of bleeding and transfusion requirements. Earlier discontinuation of aspirin results in no benefit in intermediate term survival.